2015
DOI: 10.3390/healthcare3041212
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Maternal Mental Health, Fetal Programming and Child Development

Abstract: Maternal mental disorders over pregnancy show a clear influence on child development. This review is focused on the possible mechanisms by which maternal mental disorders influence fetal development via programming effects. This field is complex since mental health symptoms during pregnancy vary in type, timing and severity and maternal psychological distress is often accompanied by higher rates of smoking, alcohol use, poor diet and lifestyle. Studies are now beginning to examine fetal programming mechanisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 77 publications
2
55
0
3
Order By: Relevance
“…Both groups of pregnant women with BD (treated and untreated with pharmacotherapy) have a greater risk for multiple adverse reproductive events (cesarean delivery, preterm birth, and infants with microcephaly, small for gestational age, and with neonatal hypoglycemia) compared to women without BD . Evolving research on the association between adversity during pregnancy (fetal programming) and life‐long health has highlighted the risks of uncontrolled disease . To contribute information on the course of BD and the impact of pharmacotherapy on symptom expression across childbearing, we conducted a prospective study of a community cohort of pregnant women with BD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups of pregnant women with BD (treated and untreated with pharmacotherapy) have a greater risk for multiple adverse reproductive events (cesarean delivery, preterm birth, and infants with microcephaly, small for gestational age, and with neonatal hypoglycemia) compared to women without BD . Evolving research on the association between adversity during pregnancy (fetal programming) and life‐long health has highlighted the risks of uncontrolled disease . To contribute information on the course of BD and the impact of pharmacotherapy on symptom expression across childbearing, we conducted a prospective study of a community cohort of pregnant women with BD.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Evolving research on the association between adversity during pregnancy (fetal programming) and life-long health has highlighted the risks of uncontrolled disease. 16,17 To contribute information on the course of BD and the impact of pharmacotherapy on symptom expression across childbearing, we conducted a prospective study of a community cohort of pregnant women with BD. We characterized symptoms of depression and mania throughout pregnancy and the first year after birth and compared symptom levels of psychotropic-treated women to those of nonpsychotropic-treated women.…”
mentioning
confidence: 99%
“…There is a need for more longitudinal studies and also those including covariates that may affect the relationship between maternal mental health in pregnancy and foetal development [3, 8]. Some prospective studies have been conducted, applying a foetal developmental programming framework, and these report of an association between maternal mood (distress, depression and anxiety) during the perinatal period and an increased risk of psychiatric symptoms in the children.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review including 43 studies found a range of outcomes from emotional, physiological, cognitive and hormonal (10). Given the vulnerability of the fetal period it is not surprising that pregnancy is emerging as a key area of interest in this literature (11,12).…”
Section: From Pregnancy To Early Childhoodmentioning
confidence: 99%